Pressure prediction model in cross laminated timber manufacturing for low-quality lumber. (November 2022) - Silva do Carmo, Dalisson Peterson; Englund, Karl; Li, Hui
Cross Laminated Timber (CLT) has been considered a feasible and sustainable option as a building material for many building applications. However, lowering costs and the ability to use a wide spectrum of lower quality lamstock can be critical for this product growth. Off-spec timber often has a significant number of out-plane defects that prevent the lamstock from lying flat and creating an intimate bond between the corresponding CLT layers. This paper aims to introduce a mechanical model to estimate the amount of pressure that makes a warped lumber flat and allow proper contact for an adhesive bond. The difference between experimental and theoretical values were less than 5 kPa for most samples analyzed. The proposed model is an important step to allowing low-quality lumber associated with out-of-plane defects to be further explored by the wood industry in order to create new options for CLT feedstock. This is especially true when considering utilization of small diameter timber (SDT), which is often not considered a viable option for many CLT lamstocks. As a desired outcome, this could minimize losses and optimize industrial manufacturing by using low-quality materials that would positively impact the forest health and mitigate wildfires, while creating economic opportunities.